2014
DOI: 10.1242/jeb.084897
|View full text |Cite
|
Sign up to set email alerts
|

Clap and fling mechanism with interacting porous wings in tiny insect flight

Abstract: The aerodynamics of flapping flight for the smallest insects such as thrips is often characterized by a 'clap and fling' of the wings at the end of the upstroke and the beginning of the downstroke. These insects fly at Reynolds numbers (Re) of the order of 10 or less where viscous effects are significant. Although this wing motion is known to augment the lift generated during flight, the drag required to fling the wings apart at this scale is an order of magnitude larger than the corresponding force acting on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
118
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(128 citation statements)
references
References 59 publications
(57 reference statements)
10
118
0
Order By: Relevance
“…4D) over a range of Re b and angles of attack. A previous study of porous wings in single wing translation also showed only a small improvement in the lift to drag ratio for a biologically relevant range (Santhanakrishnan et al, 2014).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…4D) over a range of Re b and angles of attack. A previous study of porous wings in single wing translation also showed only a small improvement in the lift to drag ratio for a biologically relevant range (Santhanakrishnan et al, 2014).…”
Section: Discussionmentioning
confidence: 79%
“…Regarding the last point, it is important to note that the horizontal force required to fling the wings apart can be an order of magnitude greater than the force required to translate a single wing (Miller and Peskin, 2009;Santhanakrishnan et al, 2014). As the wings move in opposite directions at the beginning of the fling, these forces cancel.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations